P116: Impact of young age on outcomes of emergency department procedural sedation. (May 2019) - Schlegelmilch, M.; Roback, M.; Bhatt, M.
Abstract : Introduction : Procedural sedation in the emergency department (ED) for children undergoing painful procedures is common practice, however little is known about sedation in very young children. We examined the effect of young age on sedation outcomes.Methods : This is a secondary analysis of an observational cohort study of children 0-18 years undergoing procedural sedation in six pediatric EDs across Canada. We compared presedation state, indication for sedation, medications, sedation efficacy and four main post-sedation outcomes (serious adverse events (SAE), significant interventions, oxygen desaturation and vomiting) between patients who ≤2 years with those >2 years. Pre-sedation state, medications, indication for sedation and time intervals were summarized using frequency and percentage and compared with chi2 test. Logistic regression was used to examine associations between age group and outcomes.Results : 6295 patients were included; 5349 (85%) were >2 years and 946 (15%) were ≤2 years. Children ≤2 years were sedated most commonly for laceration repair (n = 450; 47.6%), orthopedic reduction (165; 17.4%) and abscess incision and drainage (136; 14.4%). Children >2years were sedated most commonly for orthopedic reductions (3983; 74.5%). Ketamine was the most common medication in both groups, but was used most frequently in children ≤2 years (80.9% vs 58.9%; p < 0.001). There was no difference in the incidence of SAE, significant interventions or oxygen desaturation between age groups, however children ≤2 years were less likely to vomit (Table 1). Young children had decreased odds of a successful sedation (OR 0.48; 95%CI: 0.37 to 0.63). On average, patients ≤2 years were sedated for 7 minutes less (74.1 vs 81.0 p < 0.001) and discharged 10 minutes sooner (90.1 vs 100.8 p < 0.001). Table 1 ≤2 years (n = 946) >2 years (n = 5349) OR (95%CI)* p-value n(%) n(%) Serious Adverse Event 8 (0.85) 59 (1.0) 0.76 (0.43-1.7) 0.477 Significant intervention 10 (1.0) 76 (1.4) 0.74 (0.34-1.4) 0.374 Oxygen Desaturation 50 (5.3) 303 (5.6) 0.93 (0.67-1.3) 0.640 Vomiting 14 (1.5) 314 (5.9) 0.24 0.13-0.41) <0.001 *Reference category: ≤2 years.Conclusion : Children ≤2 years most commonly received ED sedation for laceration repair using ketamine. Young age was not associated with a significant difference in SAEs, significant intervention or desaturation but was associated with decreased odds of vomiting and of successful sedation.